Association of Outdoor Physical Activity and Sports with Life Satisfaction among Women of Reproductive Age According to a European Representative Sample-A Longitudinal Analysis - Viktória Prémusz; Alexandra Makai; Pongrác Ács; Evelin Derkács; Tamás Laczkó (MDPI AG, 2023)
(1) Background: Low life satisfaction (LS) is associated with impaired mental and physical health. Outdoor physical activity (PA) has diverse somatic and psychological benefits. This study aimed to analyse the associations between sports settings and LS in women of reproductive age. (2) Methods: Special Eurobarometer on Sport and Physical Activity (2022, 2018, 2013) data on regularity and settings of sports/PA, LS and sociodemographic variables were analysed. The representative sample consisted of 18,489 women (34.60 ± 9.36 years). Pearson χ2 test and multivariate logistic regression analysis were conducted, using IBM SPSS version 28.0 according to the STROBE guidelines. The significance level was set at p < 0.05. (3) There was a significant difference in LS based on sports settings (χ2 = 409.696, p < 0.001). In the outdoor group, a 21.4% higher probability of being "very satisfied" compared to the non-outdoor, 30.0% higher compared to the inactive group, was found (R2N = 0.151). Dividing the sample by age, a significant effect remained in middle adulthood (35-44 years p = 0.002 and 45-49 years p = 0.033). (4) Conclusions: Our results underline the importance of the promotion of outdoor, green exercise and the development of special interventions to maintain or improve the psychological well-being of women in reproductive age.